Gout storm - Martins, Danilo [UNESP]; Tonon, Carolina Rodrigues [UNESP]; Pacca, Rafael Lopes [UNESP]; Matchil, Natanye Lemes [UNESP]; Junior, Luiz Antonio Jorge [UNESP]; Queiroz, Dênis Silva [UNESP]; Pereira, Filipe Welson Leal [UNESP]; Silva, Alana Maia [UNESP]; Padovese, Vinicius [UNESP]; De Toledo Moraes, Marcelo Padovani [UNESP]; Da Silva, Daniel Luiz [UNESP]; Nóbrega, Vinicius Cardoso [UNESP]; et al. (International Scientific Information, 2021)
Objective: Unusual clinical course Background: Gout is a chronic disease characterized by deposition of monosodium urate crystals, typically manifesting as arthritis. Clinical presentation of gout usually results from activation of local inflammatory response. Despite being one of the oldest diseases in the world, gout pathophysiology is incompletely understood and clinical features are still surprising. Recent reports describe unusual manifestations including atypical joints involvement, tenosynovitis, panniculitis, and multinodular inguinal swelling. Another atypical feature is the acute polyarticular gout with severe systemic inflammatory response. Case Report: We report the case of a 55-year-old man presenting with fever, tachycardia, cauda equina syndrome, left-knee arthritis, and systemic inflammatory manifestations. Lumbar spine magnetic resonance imaging showed a 4.0×1.3×2.2 cm calcified mass inside the vertebral canal at the L4-L5 level, causing stenosis of the dural space and intervertebral foramen. Clinical diagnoses were septic knee arthritis and lumbar spine meningioma. Despite antibiotic therapy and left-knee surgical drainage, fever and increased C-reactive protein persisted, and arthritis developed in the elbows and right knee. As cultures were negatives, we then diagnosed gout flare in the affected joints accompanied by a severe systemic inflammatory reaction. A few days after starting colchicine and anti-inflammatory drugs, symptoms and inflammatory markers subsided. It was such a severe attack that we called it a “gout storm”. Conclusions: The report highlights the difficulty in diagnosing acute polyarticular gout affecting atypical joints, particularly when faced with a severe systemic inflammatory reaction.
Keywords: Cauda Equina Syndrome; Diagnosis; Gout